Student Teachers Experiences of Teachersa Professional Identity within the context of Curriculum Change (Global Journal of Human-Social Science, 2014)
This paper presents the findings of a qualitative case study of how 8 student teachers' experiences of teachers' professional identity within the context of curriculum change in a university in KwaZulu Natal. The students described their personal experiences in teaching during teaching practice from which two major themes stood out; the complicated demand teaching places on the student teacher and professional development. In analyzing the data, the researcher further categorized it into four themes based on emerging trends; the single self and the multiple self, becoming a teacher and teaching skills. Several shortcomings in teacher education were discovered and teacher educators and stakeholders were called upon to restructure teacher education programs based on the kind of challenges student teachers are facing. The researcher used the social constructionist theory to give meaning to the experiences of student teachers.
Keywords: teachers2019; professional identity; experiences; curriculum change; student teachers